The Feast of Corpus Christi - Walters, Barbara R. (Pennsylvania State University Press, 2006)
The feast of Corpus Christi, one of the most solemn feasts of the Latin Church, can be traced to the Fourth Lateran Council in 1215 and its resolution of disputes over the nature of the Eucharist. The feast was first celebrated in Lig̈e in 1246, thanks largely to the efforts of a religious woman, Juliana of Mont Cornillon, who not only popularized the feast, but also wrote key elements of an original office. This volume presents for the first time a complete set of source materials germane to the study of the feast of Corpus Christi. In addition to the multiple versions of the original Latin liturgy, a set of poems in Old French, and their English translations, the book includes complete transcriptions of the music associated with the feast. An introductory essay lays out the historical context for understanding the initiation and reception of the feast.